EXAMINING THE TENSION CHORDING PRINCIPLE FOR A BEAM UNDER TORSION LOAD. (May 2020) - Uttich, E. S.; Bartz, M.; Bender, B.
Abstract: Tension chording is a lightweight design principle in the human motion system. More muscles than necessary are available in this system to generate motion. By using these redundant muscles the principle contributes to the lightweight design of the motion segments. The lightweight design benefits of the principle for technical structures loaded with bending torques were shown in prior studies. This paper presents a pilot study on lightweight design benefits of using tension chording for torsion loaded structures.